Learning to teach physical education in the secondary school a companion to school experience - Capel, Susan Anne 1953-; Whitehead, Margaret 1940- (Learning to teach subjects in the secondary school series, 2015)
"The fourth edition of Learning to Teach Physical Education in the Secondary School has been revised and updated in light of the latest research evidence and practice in relation to teaching and learning, and changes in policy and practice within initial teacher education. Key topics covered include: - Starting out as a teacher - Planning and evaluation for effective learning and teaching - Communication in PE - Lesson organisation and management - Motivating pupils for learning in PENEW - Assessment for and of learning - Inclusive approaches to teaching PE - Learner-centred teaching and physical literacyNEW - Teaching safely and safety in PE - Accredited Qualifications in PE - Teacher beliefsNEW - Developing your own knowledge, skills and understandingNEW This core text guides you to become competent in basic teaching skills, enabling you to cope in a wide range of teaching situations. It emphasises the development of your own professional judgement, your ability to reflect critically on what you are doing, and on your beliefs about teaching PE. Written with university and school-based initial teacher education in mind, Learning to Teach Physical Education in the Secondary School is an essential source of support and guidance for all student teachers of PE embarking on the challenging journey to becoming an effective, successful teacher"--Provided by publisher.